Parasitoides associados a percevejos (Hemiptera : Pentatomidae) em lavouras de soja com e sem manejo integrado de pragas, no Oeste do Paraná - Favorito, Amanda Cecato (2022)
Due to the economic importance of soybean, extensive areas are cultivated under simplified management, generally based on the use of chemical products, which supports the growth of pest populations. As an example, the stink bugs of the Pentatomidae family has stood out, mainly due to its high potential to cause direct and indirect damage to the marketed product. With each harvest, there is a significant increase in its population with difficulty in managing these pests. Therefore, management practices need to be adopted more efficiently, safely and effectively, among which the integrated pest management (IPM) stands out. Associated with IPM, there is a natural biological control that directly contributes to the control of insect pests. Therefore, the objective of this study was to identify and quantify the species of stink bugs and parasitoids in soybean, in the 2019/2020 and 2020/2021 crops, in conventional and integrated pest management, in 10 counties in the western region of Paraná. The work was carried out in two areas per county, one conducted with or without the principles of IPM. Weekly collections of stink bugs and eggs were carried out at 10 points per area. Adult insects were collected with the method “pano-de-batida” and eggs were collected manually, inspecting three plants per sampling point. The insects and eggs collected were identified and monitored in the laboratory, and the parasitism was recorded. After the emergence of the parasitoids, they were stored in 90% alcohol and subsequently identified. The stink bugs collected were Chinavia sp., Diceraeus melacanthus, Edessa meditabunda, Euschistus heros, Nezara viridula, Piezodorus guildinii, Proxys sp. and Podisus sp. (Hemiptera: Pentatomidae). Of these, E. heros was the most abundant specie, representing 91.1% of the insects collected. The adults were parasitized by Hexacladia smithii (Hymenoptera: Encyrtidae), Cylindromya brasiliana, Gymnoclytia sp., Ectophasiopsis gradata, Phasia sp. and Trichopoda pictipennis (Diptera: Tachinidae). The parasitoids of eggs collected were Gryon sp., three likely species of Telenomus and Trissolcus urichi (Hymenoptera: Scelionidae). Soy management following the MIP premises did not show an increase in the number of parasitoids.